Akulturasi Budaya Islam pada Ritual Kelahiran Masyarakat Jawa di Kabupaten Oku Timur - Nashihah, Siti; Suyitno, Amin; Rochmiatun, Endang (Tadabbur: Jurnal Peradaban Islam, 2026)
This study examines the acculturation of Islamic values within Javanese birth ritual traditions, particularly the ceremonies of four-month pregnancy (telon-telon), seven-month pregnancy (piton-piton), placenta burial (mendhem ari-ari), brokohan, sepasaran, and selapasan. These traditions represent Javanese cultural heritage that has undergone a process of Islamization through the integration of Islamic teachings and religious values into their implementation. The study aims to describe the forms of birth rituals and to explain the Islamic values embedded within them. This research employed a qualitative approach using field research methods. Data were collected through observation, interviews, and documentation involving the community of Banuayu Village, Buay Madang District, East OKU Regency. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings reveal that Javanese birth rituals have acculturated with Islamic teachings through the practices of collective prayer, tahlilan, recitation of Qur’anic verses, salawat, almsgiving, and expressions of gratitude to Allah SWT. These traditions function not only as cultural heritage but also as a medium for strengthening religious values, social solidarity, and the Islamic identity of the Javanese community.